'Logrolling' in Antarctic governance: limits and opportunities - McGee, J; Arpi, B; Jackson, A (Polar Record, 2020)
The Antarctic Treaty System (ATS) is considered a successful example of international governance as it has managed tensions over sovereignty claims, avoided militarisation and dealt with marine resources and environmental protection. Recently, Chinas influence and assertiveness in many international institutions have significantly grown. What effect this shift in the international politics will have upon Antarctic governance remains to be seen. However, to further thinking on this issue we explore two current case studies that reveal pressure points within the ATS. First, in the Commission for the Conservation of Antarctic Marine Living Resources, Australia has proposed marine protected areas off East Antarctica, to which China and several other states have objected. Second, in the Antarctic Treaty Consultative Meetings, China has proposed special management arrangements for the area around the Kunlun station, to which Australia and several other states have objected. Negotiation theory suggests logrolling (i.e. trade of mutual decision-making support across issue areas) can be an effective strategy to avoid diplomatic deadlocks. We therefore consider the merits of a logrolling strategy for the above issues. We find that while a logrolling strategy in the ATS might facilitate short-term diplomatic success, it would carry significant risks, including the weakening of existing norms.